The Effect of Mutations in the TPR and Ankyrin Families of Alpha Solenoid Repeat Proteins - Izert, Matylda Anna; Szybowska, Patrycja Emanuela; Górna, Maria Wiktoria; Merski, Matthew (Frontiers in Bioinformatics, 2021)
Protein repeats are short, highly similar peptide motifs that occur several times within a single protein, for example the TPR and Ankyrin repeats. Understanding the role of mutation in these proteins is complicated by the competing facts that 1) the repeats are much more restricted to a set sequence than non-repeat proteins, so mutations should be harmful much more often because there are more residues that are heavily restricted due to the need of the sequence to repeat and 2) the symmetry of the repeats in allows the distribution of functional contributions over a number of residues so that sometimes no specific site is singularly responsible for function (unlike enzymatic active site catalytic residues). To address this issue, we review the effects of mutations in a number of natural repeat proteins from the tetratricopeptide and Ankyrin repeat families. We find that mutations are context dependent. Some mutations are indeed highly disruptive to the function of the protein .repeats while mutations in identical positions in other repeats in the same protein have little to no effect on structure or function.